Genetic and productive background of Criollo cattle in Argentina, Mexico, Uruguay and the United States - Armstrong, Eileen; Rodriguez Almeida, Felipe A.; McIntosh, Matthew; Poli, Mario Andres; Cibils, Andrés Francisco; Martínez-Quintana, José Alfredo; Félix-Portillo, Monserrath; Estell, Richard E. (Elsevier, 2022)
Cattle were first introduced to the Western Hemisphere in 1493 and by subsequent introductions from the Iberian Peninsula, providing the genetic background of the American Criollo cattle, with influences from Spanish, Portuguese and African breeds. Criollo's high adaptive capacity enabled them to spread and colonize a wide variety of environments. Their ancestry combined with local adaptations created the wide spectrum of American Criollo breeds that we see today, many currently at risk of extinction. We review the existing genetic and production data on the Argentinian, Mexican, Uruguayan and US Creole cattle that form the basis of the current and future research described in this special issue. In these countries, Criollo cattle became the basis of the livestock industry for the supply of meat, hides and animal work, until they were displaced by more specialized European and cebuine type cattle breeds at the end of the 19th century. Since then, Criollo herds remained mostly in marginal regions unsuitable for commercial breeds. Efforts by local producers and research institutions helped to preserve Criollo populations. Several studies have demonstrated that these animals can produce high quality meat and are more resistant to diseases, and emphasize their high fertility, calving ease, longevity and ability to adapt to harsh environments. Mexican Criollos have high genetic diversity but lack strong conservation programs. More detailed genetic characterization within each regional Criollo population is needed to establish appropriate conservation strategies. In US, Texas Longhorn cattle are closely related to Mexican Criollos, while Pineywoods show a stronger relationship with Iberian breeds. Variable levels of genetic diversity were found among all North American Criollos, probably due to crossbreeding. Criollos from Argentina and Uruguay showed clear divergence due to genetic isolation but clustered together, representing the southernmost expansion of bovine cattle in the Americas.